RISIKO PENERAPAN AKAD MUDHARABAH DALAM PENGELOLAAN TAMBAK UDANG (Studi Kasus: Kemukiman Gampong Lhang) - Dandi; Benazir (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2022)
The form of cooperation agreement made by managers and investors of shrimp ponds in the Gampong Lhang Village is to provide loans to managers who are considered feasible and trustworthy to manage the ponds with an agreement that the capital will be fully provided by the pond owners. The profit sharing process is explained at the time of the agreement between the pond owner and the manager, the profit sharing is 70% for the manager while 30% for the owner, but there are also some who share 40% for the owner while 60% for the manager, in this case more profit is given to the manager because of course the responsibility is heavier felt by the manager. The mudharabah contract carried out by the community is in accordance with sharia, because the basic concept of the contract is that there is an agreement between the two parties and no party is forced to enter into the cooperation agreement, therefore this contract can be said to be valid, unless there is one party who feel compelled or threatened to do the contract, then this is not allowed in Islam of course.